KAJIAN UNIT PENANGKAPAN RAWAI DI PPI SIALANG BUAH KECAMATAN TELUK MENGKUDU KABUPATEN SERDANG BEDAGAI SUMATERA UTARA - Riki Ardiansyah Nasution; Pindi Patana; Tajuddin Siregar (AQUACOASTMARINE, 2018)
Rawai is a fishing gear with the target of demersal fishes. The purpose of this research is to know the operation of longline fishery unit in terms of the construction of fishing gear, the operation and the composition of the catch and to know the productivity of fishing gear and to analyze the feasibility of longline business used by Sialang Buah fishermen. This research was conducted in PPI Sialang Buah Teluk Mengkudu Subdistrict of Serdang Bedagai District of North Sumatera for one month that is in October 2017. The research results obtained some types of fish, among others: Pari (Gymnura japonica), White Kakap (Lates Calcalifer), Grouper Epinephulus sp), Manyung fish (Netuma thalassina), Gerpu fish, Jenahar fish, Aluh fish - aluh, Red Snapper (Lutjanus malabricus), Pepeh fish. The value of the catch rate in the longline fishing gear is 277.2 kg. Business analysis for Revenue-Cost Ratio (R / C) of 1.25 which means fishing business is feasible to continue and Payback Period (PP) value is 1.4 years.Keywords: Sialang Buah, longline fishing gear, catch composition, business analysis.